German law paves the way for mandatory mediation - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2000)
Effective as of 1 January 2000, the Federal Government of Germany has introduced legislation permitting all German states (Laender) to introduce mandatory court-connected mediation with respect to certain kinds of civil disputes.